2016
DOI: 10.1007/s12640-016-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methamphetamine Exposure on Expression of Calcium Binding Proteins in Rat Frontal Cortex and Hippocampus

Abstract: Methamphetamine (METH) is a psychostimulant drug with potent effects on the central nervous system that can cause psychotic symptoms similar to those of schizophrenia. Specific alterations in GABAergic neuronal markers have been reported in schizophrenia and animal models of psychotic illness. The aim of this study was to determine whether there are changes in subpopulations of GABAergic neurons, defined by the presence of calcium binding proteins (CBPs), in animal models of METH abuse. Rats received acute (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…While diminishing numbers of CB and PV were found throughout the prefrontal cortex, striatum, and CA1–3, the selective depletion of CR found in the prefrontal cortex suggested that the vulnerability of this CBP was probably more prominent in that region. This finding was consistent with the previous study using a Methamphetamine-induced schizophrenic-like model which reported that cortical CR immunoreactivity was more vulnerable than those in hippocampal regions 42. It was suggested that GABAergic neurons expressing CR were not changed in schizophrenia 45.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While diminishing numbers of CB and PV were found throughout the prefrontal cortex, striatum, and CA1–3, the selective depletion of CR found in the prefrontal cortex suggested that the vulnerability of this CBP was probably more prominent in that region. This finding was consistent with the previous study using a Methamphetamine-induced schizophrenic-like model which reported that cortical CR immunoreactivity was more vulnerable than those in hippocampal regions 42. It was suggested that GABAergic neurons expressing CR were not changed in schizophrenia 45.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the schizophrenic-like model in the neuroprotective effect study and in the cognitive enhancement effect study had decreases in CB and PV immunoreactivity neurons in the prefrontal cortex, striatum, and CA1–3. Deficits of both CB and PV immunoreactivity were previously reported in the frontal cortex from the schizophrenic-like model 4042. Deficits in PV immunoreactivity were also investigated in the hippocampus of both schizophrenic-like models and patients 4244.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the longer term the drug can have neurotoxic effects on several neurotransmitter systems, including that of GABA [4,5]. This has recent support both from pharmacogenetic studies of association between METH psychosis and polymorphisms in the GABA synthetic enzyme glutamate decarboxylase (GAD) genes [6] and from findings, in an animal model of METH abuse, of deficits in, most strongly, the parvalbumin (PV)containing subtype of GABergic neurons in frontal cortex and hippocampus [7].…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, in support of the key role of PV deficits in modelling schizophrenia, we and others have demonstrated this pathology in a range of other rodent models, developmental and pharmacological, that can produce behavioural deficits modelling certain aspects of schizophrenia. These include isolation rearing (Harte et al, 2007), prenatal or neonatal inflammatory challenge with lipopolysaccharide (Jenkins et al, 2009; Wischhof et al, 2015) and chronic or acute high-dose methamphetamine (Veerasakul et al, 2016). Others have observed PV neuronal losses following prenatal methylazoxymethanol (Penschuck et al, 2006) or repeated ketamine administration (Sabbagh et al, 2013).…”
mentioning
confidence: 99%